ZTD em tempo quase real via Estações GNSS Terrestres: estratégia de processamento para o GIPSY-OASIS II e combinação das séries temporais - Rofatto, Vinicius Francisco [UNESP] (2013)
One of meteorological products obtained from the high-precision GNSS data processing is the zenithal tropospheric delay, which can be used to quantify the integrated water vapor, an important measurement for atmospheric sciences. Combination of tropospheric delay time series aims to generate a single solution, more reliable than each individual series. This dissertation proposes a combination in near real time of tropospheric delay parameters based on multiple solutions for a specific time. Under these circumstances, it was decided a combination derived by the least squares method and the quality control process based on detection, identification and adaptation. The zenithal tropospheric delay was derived by GIPSY-OASIS II and GAMIT GNSS data processing software systems, each one using different processing methods and strategies...